Debt Financing dan Dampaknya terhadap Perkembangan Usaha Mikro di Bogor - Jaenal Effendi; Ditta Wardhani (Department of Islamic Economics, IPB University, 2016)
Micro and small enterprises (MSEs) have an important role in supporting the national economy. Nevertheless, MSEs still have a major problem in its development, called limited capital. The presence of BPRS which is part of sharia financial institutions is expected to provide financing assistance for MSEs. The financing provided by BPRS is not only given in the form of equity financing but also in the form of debt financing. This study analyzes the effect of debt financing on MSEs development and also the factors influenceing the income and profit of MSEs after getting debt financing. The method used in this research is paired sample t test and Ordinary Least Square (OLS). The result of paired sample t test showed that the variable of earnings and profit of MSEs have significant change after getting financing. Furthermore, the result of analysis with OLS method showed that labor variable, amount of financing, profit rate, gender dummy, and education dummy have a significant effect to earnings and profit of MSEs